EFFECT OF OVSYNCH TREATMENT ON BLOOD BIOCHEMICAL CONSTITUENTS AND CONCEPTION RATE IN RETAINED FETAL MEMBRANES AFFECTED AND NORMALLY CALVED COWS - VELLADURAI, C; EZAKIALNAPOLEAN, R; SELVARAJU, M; DORAISAMY, K A (The Indian Journal of Animal Reproduction, 2023)
Eight cows treated (Group I) for retained fetal membranes (RFM) and 8 normally calved (NC) cows(Group II) were selected around day 35-50 post-partum and were supplemented orally daily with 30-50 gmineral mixture continuously for 15 days. At the end of mineral mixture supplementation, all the cows of boththe groups were treated with ovsynch protocol. The mean blood glucose, serum total protein, cholesterol,triglycerides, calcium and phosphorus levels were found to be lower in RFM affected cows than NC cows ati) the time of animal selection (ii) the initiation of ovsynch treatment (iii) PGF p injection (iv) Timed artificialinsemination (TAI) and (v) 10 days following TAI. Further, in both the groups, there was an increasing trend in allthese blood constituents from selection to 10 days post Al. The conception rate obtained was 87.50 and 75.00per cent, respectively. It is concluded that ovsynch programme influenced the levels of blood constituents andimproved conception rate in RFM affected and NC cows.
Keywords: Ovsynch; Blood biochemical constituents; RFM; Cows